2006
DOI: 10.1080/10349120600847706
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Phonological Awareness and Letter Knowledge in Preschool Children with Down Syndrome

Abstract: This study investigated the effectiveness of a phonological awareness intervention for 4-year-old children with Down syndrome. Seven children with Down syndrome who attended an early intervention centre participated in the intervention. Their performance on measures of phonological awareness (initial phoneme identity), letter name and sound knowledge, and print concepts preintervention and post-intervention, was compared with that of a randomly selected group of agematched peers with typical development. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 53 publications
3
63
0
2
Order By: Relevance
“…Caregiver-Implemented Shared-Reading Interventions: Implementation Barriers For children with LI, efforts to improve their earlyliteracy skills and reduce their risk for future RD often feature caregiver-implemented shared-reading interventions in the home environment (Crain-Thoreson & Dale, 1999;Dale, Crain-Thoreson, Notari-Syverson, & Cole, 1996;Ezell, Justice, & Parsons, 2000;Justice et al, 2005Justice et al, , 2011van Bysterveldt et al, 2006). Doing so provides an avenue for actively involving caregivers in their children's intervention, improving the home literacy environment that children experience, and using an empirically validated practice to address children's risk for RD.…”
Section: The Theoretical Domains Framework From the Field Of Implemenmentioning
confidence: 99%
See 1 more Smart Citation
“…Caregiver-Implemented Shared-Reading Interventions: Implementation Barriers For children with LI, efforts to improve their earlyliteracy skills and reduce their risk for future RD often feature caregiver-implemented shared-reading interventions in the home environment (Crain-Thoreson & Dale, 1999;Dale, Crain-Thoreson, Notari-Syverson, & Cole, 1996;Ezell, Justice, & Parsons, 2000;Justice et al, 2005Justice et al, , 2011van Bysterveldt et al, 2006). Doing so provides an avenue for actively involving caregivers in their children's intervention, improving the home literacy environment that children experience, and using an empirically validated practice to address children's risk for RD.…”
Section: The Theoretical Domains Framework From the Field Of Implemenmentioning
confidence: 99%
“…To this end, a number of researchers have studied avenues for improving the early-literacy skills of young children with LI, with many studies finding positive short-term effects (Gillon, 2002;Justice, Chow, Capellini, Flanigan, & Colton, 2003;Justice, Kaderavek, Bowles, & Grimm, 2005;Lovelace & Stewart, 2007;van Bysterveldt, Gillon, & Moran, 2006). The prevailing approach to improving earlyliteracy skills, as applied to children with LI and children at risk more generally, involves systematic manipulation of shared-reading routines so as to make early-literacy learning opportunities more salient and intensive for children.…”
mentioning
confidence: 99%
“…Both phonological awareness and phonological memory have been found to be impaired in individuals with DS (Boudreau, 2002;Cossu, Rossini, & Marshall, 1993;Fowler et al, 1995;Kay-Raining Bird et al, 2000;Lemons & Fuchs, 2010). Research examining phonological awareness in DS has indicated deficits when compared to TD controls matched on reading ability (Cardoso-Martins & Frith, 2001;Cardoso-Martins, Michalick, & Pollo, 2002;Cossu et al, 1993;Gombert, 2002;Roch & Jarrold, 2008;Snowling, Hulme, & Mercer, 2002), even when controlling for cognitive ability (Snowling et al, 2002;Verucci et al, 2006) and when compared to controls matched on mental-age (Boudreau, 2002) or chronological age (van Bysterveldt, Gillon, & Moran, 2006). The deficit in phonological awareness has also been found across a huge age range in DS, from as young as 5.5 years upwards to 49 years (Boudreau, 2002;Cardoso-Martins & Frith, 2001).…”
Section: Phonological Processing Research On Phonological Recoding Imentioning
confidence: 99%
“…Growing research evidence demonstrates that -when provided with the opportunity to learn -children with Down syndrome develop PA and phonic decoding skills (Burgoyne et al, 2012;Cologon et al, 2011;Cohen et al, 2008;Cupples & Iacono, 2002;Goetz et al, 2008;van Bysterveldt, Gillon, & Moran, 2006) and can demonstrate advanced reading development. In addition, research with children aged between 2 and 12 years shows that reading intervention targeting PA and phonic decoding skills results in improved articulation of words (Cologon, 2008).…”
Section: Pa and Phonic Decoding Skills In Children With Down Syndromementioning
confidence: 99%